A newly designed disk-lobe occluder with isogenous barbs for left atrial appendage closure: Initial multicenter experience - Bai, Yuan; Tang, Xuechao; Xu, Xudong; Zhao, Xianxian; Xu, Yawei; Chen, Wei; Zhu, Xianyang; Wang, Qiguang; Han, Zhihua; Wang, Changqian; He, Lu; Zhang, Yushun; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: Although the implant success rate of left atrial appendage closure has increased and complications have decreased over time, there are still anatomically and technically complicated cases where novel LAA occluders may simplify the procedure and thus might potentially improve the clinical outcome. Objectives: This study aimed to assess the safety and efﬁcacy of the newly designed device with isogenous barbs in LAAC. Methods: Eight centers in China participated in this prospective study from July 2016 to April 2018. Peri- and post-procedural safety and efficacy were evaluated through scheduled follow-ups and transesophageal echocardiography (TEE). Results: A total of 175 patients with a mean age of 68.4 ± 9.2 years old, a mean CHA2DS2-VASc score of 4.7 ± 1.8, and a mean HAS-BLED score of 3.2 ± 1.3, were included. The device was successfully implanted in 173 patients (98.9%). The device size ranged from 18mm to 34mm. Clinically relevant pericardial effusion in the perioperative period, occurred in 3 patients (1.7%). TEE follow-up was available in 167 (96.5%) patients at 12-month. During follow-up, 9 patients suffered serious adverse event: 4 death (2.3%), 1 ischemic stroke (0.6%), and 2 gastro-intestinal bleeding (1.2%) and 2 device-related thrombus (1.2%). Estimated annual thromboembolism rate reduced by 90% and estimated annual major bleeding rate reduced by 81% after LAAC with the newly designed device. Conclusions: The newly designed device with isogenous barbs for LAAC could be performed effectively with a low incidence of adverse events and a high incidence of anatomic closure.